High viral infection rates in Antarctic and Arctic bacterioplankton - Sawstrom, C; Graneli, W; Laybourn-Parry, J; Anesio, AM (2007)
The frequency of visibly phage-infected bacterial cells (FVIB) and the average number of phages per cell [i.e. burst size (BS)] were determined in Antarctic and Arctic ultra-oligotrophic freshwater environments. Water samples were collected from two Antarctic freshwater lakes and cryoconite holes from a glacier in the Arctic. Data from this bipolar study show the highest FVIB (average 26.1%, range 5.1% to 66.7%) and the lowest BS (average 4, range 2–15) ever reported in the literature. The bacterial density is low in these ultra-oligotrophic freshwater environments but a large proportion of the bacteria are visibly infected. Our results suggest that a constant virioplankton population can be maintained in these extreme environments even though host density is low and often slow growing.